A Comparative Study of The Clinical and Radiological Features of Pulmonary Tuberculosis in Individuals with And Without Diabetes - Murthy, V Narayana; Reddy, K Sai Yaswanth; Mayilananthi, Mayilananthi (Journal of Neonatal Surgery, 2025)
Background People with diabetes are three times more likely to develop tuberculosis than those without diabetes. The clinical presentation and response to treatment in diabetic patients exhibit distinct patterns compared to non-diabetic individuals. This research focused on examining the clinical and radiological characteristics of pulmonary tuberculosis in patients with diabetes compared to those without diabetes. Methods This study was conducted in the General Medicine Department at Chettinad Hospital and Research Institute in Chennai. It included two groups: diabetic patients with pulmonary tuberculosis and non-diabetic patients with the same condition. All participants provided written informed consent prior to the study. Results The analysis comprised 163 participants, with 79 individuals from the diabetic cohort and 84 individuals from the non-diabetic cohort. Within diabetic group, the radiology observations were as follows: 19% exhibited cavitary lesions, 39.2% showed consolidation, and 13.9% had fibro-cavitary lesions. In contrast, the non-diabetic group presented the following radiological findings: 10.7% with cavitary lesions, 29.8% with consolidation, and 9.5% with fibro-cavitary lesions. Conclusion The research indicated that the clinical manifestations of tuberculosis were largely similar between diabetics and non-diabetics. However, notable differences were observed in the radiographic presentation of tuberculosis among diabetic patients, who demonstrated a higher prevalence of cavitation and a more extensive involvement of the lower lung lobes, in contrast to the upper lobe involvement that was more frequently observed in non-diabetic patients